Clinical features and outcomes of pseudolithiasis induced by ceftriaxone in Chinese children: a single-center observational study - Jin, Chen; Xiu, Wen-Li; Liu, Yao; Hao, Xi-Wei; Dong, Qian (Frontiers in Pediatrics, 2025)
IntroductionCeftriaxone (CTX) is widely used in pediatric infectious disease treatment, although the diagnostic and therapeutic management of CTX-induced gallbladder pseudolithiasis (PL) remains challenging. In this study, we investigated the occurrence, clinical features, and management of CTX-induced PL in children.MethodsA retrospective case-control study was conducted on 185 pediatric patients receiving CTX at a single center. Data on treatment regimens, gallbladder imaging findings, and serum biochemical parameters post-CTX therapy were analyzed. Patients were classified into PL (n = 34) and non-PL (n = 151) groups based on imaging findings.ResultsPL was diagnosed in 18.4% of patients treated with CTX, primarily through ultrasound, which revealed hyperechoic material within the gallbladder. Compared with the non-PL group, patients with PL were older and taller, with no significant differences in CTX dosage (p = 0.915). Patients with PL also had higher rates of digestive and neurological infections (both p < 0.001). Serum analysis revealed distinct liver and kidney function markers in the PL group, including lower levels of total bile acids, adenosine deaminase, and lactate dehydrogenase, and higher creatinine levels (all p < 0.05). Discontinuation of CTX led to symptom resolution in most cases, and all cases of PL resolved within three months.ConclusionsThe occurrence of PL is not significantly related to CTX dosage. Furthermore, the rate of CTX metabolism and excretion may play a key role in PL development. Overall, the findings demonstrate that ultrasound is an effective tool for monitoring the development of PL in children receiving CTX and that discontinuation of CTX could be an effective treatment for PL.